Recent Progress in Protein 3D Structure Comparison - Carugo, O.; Pongor, S. (Current Protein and Peptide Science, 2002)
Quantitation of protein 3-D structure similarity is crucial in such fields as evolutionary studies, structural modeling and prediction of biological function. There are various approaches, many of which are tailored to specific problems. This review summarizes the recent developments in this field with particular interest in two main areas: i) improvements to and statistical interpretation of the root-man-square distance between equivalent atoms, rmsd, and ii) methods of protein structural classification based on geometrical features. Special attention is given to fast methods capable of analyzing large structural databases.
Keywords: root-man-square